2015
DOI: 10.1103/physrevc.92.054912
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic hydrodynamics for a mixture of quark and gluon fluids

Abstract: A system of equations for anisotropic hydrodynamics is derived that describes a mixture of anisotropic quark and gluon fluids. The consistent treatment of the zeroth, first and second moments of the kinetic equations allows us to construct a new framework with more general forms of the anisotropic phase-space distribution functions than those used before. In this way, the main difficiencies of the previous formulations of anisotropic hydrodynamics for mixtures have been overcome and the good agreement with the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 45 publications
(81 reference statements)
4
37
0
Order By: Relevance
“…Tests of this formulation are performed by comparing the results of anisotropic hydorodynamics with the exact solutions of the Boltzmann equations for a mixture of fluids in the Bjorken flow limit. One finds a very good agreement between the hydrodynamic and kinetic-theory results [1]. …”
supporting
confidence: 58%
See 1 more Smart Citation
“…Tests of this formulation are performed by comparing the results of anisotropic hydorodynamics with the exact solutions of the Boltzmann equations for a mixture of fluids in the Bjorken flow limit. One finds a very good agreement between the hydrodynamic and kinetic-theory results [1]. …”
supporting
confidence: 58%
“…The equilibrium distribution functions are used to define the RTA collision terms in (1). In this case µ and T should be treated as the effective baryon chemical potential and effective temperature that are determined by the appropriate Landau matching conditions.…”
Section: Kinetic Equationsmentioning
confidence: 99%
“…In Minkowski space with 1 Previous studies of the Bjorken model have shown that after rewriting the hydrodynamical equations for the temperature and the only independent component of the shear viscous tensor in terms of the variable w ¼ τTðτÞ (where τ and T are the longitudinal proper time and temperature) reduce effectively to a truly 1D nonlinear differential equation [20,26,27,36,37]. The solution of this equation for a suitable initial condition determines what has been, by abuse of terminology, called the "attractor solution."…”
Section: Setupmentioning
confidence: 99%
“…Previous works have focused on fluids undergoing Bjorken flow [20,26,27,36,37] and nonhomogeneous expanding plasmas [39]. We expand these studies by investigating the properties of the attractors in the plasmas undergoing Gubser flow [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is the entropy equation (with a non-vanishing source term, as entropy must grow in non-equilibrium situations) [27]. But in principle, also higher moments of the Boltzmann equation could serve to determine the anisotropy parameter [33][34][35].…”
Section: Introductionmentioning
confidence: 99%